Attack of the 50-foot Fly Guy - Arnold, Tedd (Arnold, Tedd. Fly Guy., 2019)
When Fly Guy snacks from a radioactive trash can, he grows until he is fifty feet tall--and Buzz has to find out a way to counteract the effect before the army attacks his pet.